TOLERANSI BERAGAMA DAN KARAKTER BANGSA: PERSPEKTIF ARKEOLOGI - Hariani Santiko (Jurnal Sejarah dan Budaya, 2013)
Abstract. The cultural intolerance occurs in our country. Horizontal conflicts involving religion and ethnicity happen frequently at several regions. The cultural values, especially tolerance value, is on the declined or disappeared? Tolerance value, as one of virtue values or even as our nation basic character, is as value transmitted from one generation to next generation. By historical examples and socializing past values through lesson of Pancasila can be internalized effectively values of nation character building.